Charakterystyka i potencjał innowacyjny gospodarstw typu rodzinnego w Polsce - Darrot, Catherine; Mouchet, Christian (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2005)
Preliminary interviews concerning 20 farms in the regions of Podlasie and Małopolska were carried in 2003 for a doctorate entitled "Interest and future of Polish peasant-like farming systems in European development models: an ethno-agronomical and socio-economic approach ". In farms where less than 15 ha are available complementary incomes are necessary. They can be provided either by social transfers, either by salaried work. A precise repartition of tasks on the farm between specific feminine (manual work and provision of subsistence goods) and masculine (mechanized work and production for sale) tasks, explain different evolutions of production depending on access to outside jobs by each member of the couple. Agronomical organization of the farm was also described, with four parts which can be distinguished in traditional farming systems: family garden, field crops, permanent pastures and private forest, and an ecologically positive impact of agronomical techniques observed. These family-like farming systems can be considered as innovating in context of the contemporary European debate about ecological and economical choices in agriculture, also represented by other groups of fanners in Europe. In the future this could encourage the autonomy and the reduction of inputs employed in the Polish family-run farms, with their new orientations on the European financial help.